Max and Zoe at the School Concert - Sateren, Shelley Swanson; Sullivan, Mary, 1958- (Oxford : Raintree, 2020)
Max is worried about singing in the school concert, so his best friend Zoe offers to help him practice.
Keywords: Readers -- Fiction; Children's stories, English; Concerts -- Juvenile fiction; Singing -- Juvenile fiction; Friendship -- Fiction